Letter (copy) : Scottish Ambulances in Spain - Tewson, Vincent
042-0052-001 Secretary's HVT/FC/EK/1093. 19th May, 1938. Sir Daniel Stevenson, Bart., LL.D., The Scottish Ambulance Unit in Spain, 5, Cleveden Road, GLASGOW, W.2. Dear Sir Daniel, SCOTTISH AMBULANCES IN SPAIN Your letter of the 17th instant has arrived while Sir Walter is away from the office on business, but I am sure he will be interested to learn upon his return of the details of your report. Yours sincerely, Assistant Secretary. 292/946/42/52